2009
DOI: 10.1017/s1751731109004121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three PCR-based methods to detect a Piedmontese cattle point mutation in the Myostatin gene

Abstract: Despite many recent advances in single nucleotide polymorphism (SNP) genotyping technologies, there is still the need for methodologies with a reasonable throughput. In this study, we compared three PCR-based methods for SNP detection: (1) a conventional PCR-based allele detection system with fluorescent genotyping technology, (2) a SNaPshot methodology by single nucleotide primer extension and, (3) a real-time PCR-based method by allele-specific minor groove-binder probes. These three methodologies were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Animals with this phenotype have a significantly greater percentage of muscle than those with the wild-type genotype, and thus produce more meat at slaughter (Wiener et al 2009), suggesting that this characteristic has been strongly selected in these breeds due to its positive association with meat production capacity. The Piedmontese breed carries at high frequency a nonsynonymous mutation in myostatin (Kambadur et al 1997;McPherron and Lee 1997;Pozzi 2009), rather than the 11-bp deletion found in the Belgian Blue, Asturiana de los Valles, and South Devon breeds.…”
Section: The Myostatin Gene Region In Cattlementioning
confidence: 90%
“…Animals with this phenotype have a significantly greater percentage of muscle than those with the wild-type genotype, and thus produce more meat at slaughter (Wiener et al 2009), suggesting that this characteristic has been strongly selected in these breeds due to its positive association with meat production capacity. The Piedmontese breed carries at high frequency a nonsynonymous mutation in myostatin (Kambadur et al 1997;McPherron and Lee 1997;Pozzi 2009), rather than the 11-bp deletion found in the Belgian Blue, Asturiana de los Valles, and South Devon breeds.…”
Section: The Myostatin Gene Region In Cattlementioning
confidence: 90%
“…PCR based methods, such as PCR based allele detection system (AS-PCR) and fluorescent gene detection technology, allele specific small groove binding probe real-time PCR detection (RT-PCR), PCR restriction fragment length polymorphism (RFLP), polymerase chain reaction single strand conformation polymorphism (PCR-SSCP) and heteroduplex mobility analysis (HMA) belong among the most commonly used point mutation detection methods ( Callens and De Clercq, 1999 ; Pozzi et al, 2009 ; Riahi et al, 2015 ; Prykhozhij et al, 2018 ).…”
Section: Traditional Point Mutation Detection Methodsmentioning
confidence: 99%